PERILAKU POLA MAKAN SEHAT MENGURANGI RISIKO DIABETES DI DESA SIDODADI KELURAHAN SETERIO KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN TAHUN 2022 - Rima Ernia; Muslimin Muslimin; M. Nabil M. Nabil; M. Fakhrudin Al Yahya Al Yahya (Institut Pendidikan Tapanuli Selatan, 2022)
Diabetes mellitus (DM) is a disease that causes death which is characterized by hyperglycemia. T2DM is a metabolic disease caused by insulin resistance and pancreatic beta cell dysfunction. The dominant lifestyle that triggers T2DM is diet and physical activity. Sidodadi Village is an urban area, generally has an urban lifestyle, which experiences the ease of technology making lifestyle changes, especially diet and lack of physical activity. This condition is the idea of ​​research on lifestyle maintenance and diabetes prevention. The results showed that on average people had normal blood sugar levels, as many as 10 people, and 4 people who had high blood sugar levels. Of the 15 people who did the examination/test for blood sugar levels, there was 1 person who had blood sugar levels called Prediabetes. The existence of continuous education about diabetes, its causative factors and a healthy lifestyle has provided changes in improving healthy lifestyles. After this PKM activity ends, it is hoped that it will increase the knowledge of the people of Sidodadi Village regarding the management of diabetes.